The problem is..... (tan[theta] + cot[theta])^2=sec^2[theta] + scs^2[theta]
Originally Posted by kennysbaby28
solved....
(tan[theta] + cot[theta])^2=
=(tan[theta])^2 +2(tan[theta]) ( cot[theta]) +(cot[theta])^2
=(tan[theta])^2 +2(sin[theta]/cos[theta])(cos[theta]/sine[theta]+(cot[theta])^2
=(tan[theta])^2 +2+(cot[theta])^2
={(tan[theta])^2 +1}+{(cot[theta])^2+1}
an we know
(tan[theta])^2 +1=sec^2[theta] and
(cot[theta])^2 +1=csc^2[theta]
then
(tan[theta] + cot[theta])^2=sec^2[theta] + csc^2[theta]